Budaya Organisasi Sebagai Strategi Pengelolaan Konflik dalam Perusahaan Keluarga di PT. Book Mart Indonesia - Dian Rokhmawati; Rachma Yuliana (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2021)
Conflicts in family companies cannot be avoided, given that there are stronger emotional factors in employee family ties that are integrated with logic and rational targets in doing business. For this reason, a conflict management strategy is needed that makes conflict a supporter of the strength of the family business. This study aims to: 1) Determine the extent to which conflict affects the activities and business performance of the company, and 2) how the strategy of PT. Book Mart Indonesia in managing conflicts that occur. The approach used in this research is qualitative, while the type of research is descriptive. The determination of the source in this study was carried out by means of purposive sampling. Two types of data used are primary data and secondary data. Data collection procedures used were interviews and documentation. The results showed that the root causes of conflict in PT. Book Mart Indonesia (PTBMI) is a company that is empty of family values, no organizational culture and weak corporate vision and mission. Conflicts that occur (media.neliti.com), for example misunderstandings related to information, decisions related to project making and decisions about task shifting / division of labor. This conflict is caused by the absence of Standard Operating Procedures (SOP), the absence of clear company rules such as an administrative system (recording), professional financial management to strengthening brands in the market. This conflict has a major impact, with indications of high employee turnover and a decline in company performance. Keywords : Conflict, Family Company, Organizational Culture, Strategy, Management.